The Influence of Competency and Compensation on Employee Performance at the Bima City Cooperatives, Industry and Trade Department - Zihan Saputra (Pustaka Digital Indonesia, 2024)
This study investigates the impact of competency and compensation on employee performance at the Bima City Cooperatives, Industry, and Trade Department. The research aims to determine: 1) if competency significantly influences employee performance, 2) if compensation significantly influences employee performance, and 3) if both competency and compensation simultaneously influence employee performance. An associative research design was employed, utilizing data collection methods such as interviews, observations, questionnaires, and literature reviews. The data were analyzed using various statistical tests including validity and reliability tests, classical assumption tests, multiple linear regression analysis, correlation coefficient analysis, coefficient of determination, and t-tests (partial) and F-tests (simultaneous). The findings reveal that competency significantly influences employee performance at the Bima City Cooperatives, Industry, and Trade Department. Similarly, compensation significantly affects employee performance. Moreover, competency and compensation together have a significant impact on employee performance. These results suggest that the Bima City Cooperatives, Industry, and Trade Department should focus on enhancing competencies related to knowledge and skills, as well as providing adequate compensation and facilities to motivate employees to perform better. The study recommends that future research consider additional variables such as work training and motivation, which were not included in this study. By addressing these factors, the department can further improve employee performance and achieve organizational goals more effectively.